2014
DOI: 10.1007/s00737-014-0415-x
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal fear of childbirth and sense of coherence among healthy pregnant women in Japan: A cross-sectional study

Abstract: While antenatal fear of childbirth (FOC) has been associated with many psychosocial variables, few studies have focused on individual stress resiliency. Sense of coherence (SOC) is one of the essential components of individual stress resiliency. This study investigates the relationship between antenatal FOC and SOC in Japanese healthy pregnant women. Self-reported questionnaires were distributed to 240 women at 37 gestational weeks at an obstetric clinic in Tokyo, Japan. Structural regression modeling was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 32 publications
2
22
0
4
Order By: Relevance
“…Three studies did not include data that could be included in the meta‐analysis and two studies included the same population as a third study . A brief summary of the studies not included in the meta‐analysis is presented in Table .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies did not include data that could be included in the meta‐analysis and two studies included the same population as a third study . A brief summary of the studies not included in the meta‐analysis is presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, many of the studies included in the systematic review were of a cross-sectional design that only capture FOC at one point in time during pregnancy (see Table 1). It is possible that questionnaires may not be applicable in different countries and in other cultural contexts (even in the same language) as psychometric aspects of the tool may be lost (14), hence tools should be specifically validated for use in each country (14,52). This is a limitation of our study as we included studies that used various questionnaires administered in different languages (52).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, low SOC scale scores were related to higher anxiety [25] and depression [28], and it was reported that SOC scale score was negatively linked with antenatal fear of childbirth: A high SOC scale score works as a resiliency factor that helps pregnant women cope with the stress of their upcoming childbirth and reduces fear of childbirth [40]. Furthermore, it was shown that the stress status during early pregnancy affects the pregnancy course and the health of the fetus [41], and that maternal complications were related to low SOC scale scores [42].…”
Section: Discussionmentioning
confidence: 96%